Growth of Cymbidium ensifolium (L.) Sw. with the Application of Mycorrhizal Fertilizers - Misrofah, Sofatu; Setiari, Nintya; Nurchayati, Yulita; Suedy, Sri Widodo Agung (Jurnal Hortikultura Indonesia, 2022)
ABSTRACT Cymbidium ensifolium is a terrestrial orchid listed on CITES 2020 as an endangered or vulnerable species that requires ex situ conservation. One of the supporting factors for orchid cultivation is the application of fertilizer. Mycorrhizal biofertilizers are eco-friendly and can reduce the negative impact of inorganic fertilizers. This study aims to examine the effect of various doses of mycorrhizal biofertilizers on the growth of C. ensifolium. This study was arranged using a one-factor Completely Randomized Design, namely mycorrhizal biofertilizers (0; 5; 10; 15 g plant-1) with 6 replications. Data were analyzed in the Analysis of Variance with a 95% confidence level. The experiment was conducted from October 2021 – February 2022 in Tembalang, Semarang. Parameters observed were time of shoot emergence, number of shoots, time of leaf emergence, number of leaves, and the percentage of mycorrhizal infections. The results showed that the treatment of mycorrhizal biofertilizers had a significant effect on the time of emergence of shoots and leaves, the number of leaves, and the percentage of mycorrhizal infections. Mycorrhizal biofertilizer at 5 g plant-1 is the optimal treatment to increase the time of emergence of shoots and leaves, and the optimal concentration of 15 g plant-1 increases the number of leaves and the percentage of mycorrhizal infections. The effect of this mycorrhizal biofertilizer can be developed for the preservation of other types of orchids. Keywords: orchid species, Cymbidium, biofertilizer, mycorrhiza